Runup of solitary waves on high strength steel mesh rock mattress revetments: Experiments and empirical equations - Mohammad Heidarzadeh; Mahan Sheibani; Roberto J. Luis-Fonseca; Felix Nowak (Results in Engineering)
For the first time, we developed empirical equations for the runup of solitary waves on high-tensile strength steel mesh revetments. This innovative coastal protection system, known as the Tecco Cell (TC) revetment, consists of rock mattresses enclosed in high-tensile, stainless, and highly flexible steel mesh. The TC revetment was successfully implemented along a UK coastline in 2016 and has been providing effective protection since. Due to the limited understanding of the hydraulic performance of this system, we conducted laboratory experiments to develop runup equations under solitary wave conditions. Results show that the dimensionless runup (runup divided by incident wave height) increases with the surf similarity parameter, following a power-law trend with an exponent close to 0.4. An alternative runup law was also proposed, relating the dimensionless runup (runup divided by water depth) to slope angle, incident wave height, and water depth. For practical application, it is recommended to use the average of the two runup values, although engineers may select either based on professional judgment. To aid implementation, two nomograms have been developed corresponding to the two runup relationships. As a pioneering study, this research is expected to stimulate further investigations into rock mattress revetments and significantly advance their design and applications.